Person-Centered Healthcare Practice in a Pandemic Context: An Exploration of People's Experience of Seeking Healthcare Support - Curnow, Eleanor; Tyagi, Vaibhav; Salisbury, Lisa; Stuart, Kim; Melville-Jóhannesson, Barbara; Nicol, Kath; McCormack, Brendan; Dewing, Jan; Magowan, Ruth; Sagan, Olivia; Bulley, Cathy (Frontiers in Rehabilitation Sciences, 2021)
Background: The recent COVID-19 pandemic increased pressure upon healthcare resources resulting in compromised health services. Enforced national lockdown led to people being unable to access essential services in addition to limiting contact with social support networks. The novel coronavirus, and subsequent condition known as long covid were not well understood and clinicians were not supported by existing guidelines or pathways. Our study explored people’s experiences of healthcare during this period with a person-centered ‘lens’. Method: 97 people participated in our online survey about their experiences of the pandemic, particularly while socially isolated and their experiences of healthcare. Following completion of the survey, eleven of these participants agreed to further semi-structured interviews to explore this further in their own words. Interview conversations were transcribed, checked; together with the responses to open questions in the survey. The data were then analyzed thematically by members of the research team. We conducted framework analysis from a post-positivist perspective, using the Person-centered Practice Framework to explore participants’ experiences. Results: There were few examples of people describing person-centered care. People experienced barriers to accessing support, and negative experiences of care that represented complexities enacting person-centered care at each level of the framework (processes, practice environment, prerequisites, macro context). These barriers were influenced greatly by the pandemic, for example, with health professionals being harder to access. Some experiences related to the ways in which health professionals responded to the context, for example, positive examples included active listening, recognition of people’s experiences, seeking to find out more, and engaging in collaborative problem-solving. Discussion: People want to feel heard, supported to navigate healthcare systems, source trustworthy information, find appropriate services, and collaborate in learning and problem-solving with healthcare professionals. There have been enormous challenges to the provision of healthcare throughout the pandemic. Moving forward is crucial with emphasis on overcoming barriers to person-centered healthcare. This should focus on steps now and also in planning for the possibility of further rapid changes in the demand for and provision of healthcare.